STRES KERJA DAN TURNOVER INTENTION PERAWAT DI RUMAH SAKIT DI JAWA TIMUR - Santoso, Windu; Sri Sudarsih (Jurnal Perawat Indonesia, 2024)
Nurses who work to provide nursing care to patients experience various stressors and stress is known to be an important predictor of nurses' turnover intentions. The aim of this study was to determine the relationship between job stress and turnover intention of nurses in hospitals in East Java. Research design uses correlation analytics with a cross-sectional study. The samples in this study were nurses in various hospitals in East Java. The sampling technique used in this research was purposive sampling. The sample consisted of 190 respondents. Data collection using a questionnaire consisted of a questionnaire for job stress and a questionnaire for turnover intentions. Statistical test using chi square. This study showed that of the 53.7% of respondents with high job stress who had the intention to move, there were 71 respondents (37.4%). The higher the job stress, the higher the turnover intention. The results of statistical tests show that there is a relationship between job stress and turnover intention with p = 0.047. One of the causes of intention to move is job stress. job stress is felt by nurses as pressure when completing a task. so they may choose or have the intention to leave the workplace.